2014
DOI: 10.1021/jp509780f
|View full text |Cite
|
Sign up to set email alerts
|

Probing Metal-Bridging Oxygen and Configurational Disorder in Amorphous Lead Silicates: Insights from 17O Solid-State Nuclear Magnetic Resonance

Abstract: The detailed degree of mixing between framework Si and metal cations and the nature of oxygen that only links metal cations (metal-bridging oxygen) in archetypal metal oxide glasses have been among the unsolved problems in physical chemistry. Binary lead silicate (PbO-SiO2) glass is an ideal model system for exploring the extent of cation disorder and metal-bridging oxygen because of its peculiar glass-forming ability at high PbO concentration. Here we report the first high-resolution 17O solid-state NMR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 74 publications
(227 reference statements)
10
57
0
2
Order By: Relevance
“…Through the comparison undertaken on lead silicates glasses and lead silicates crystals by Furkawa et al (1978) and on lead oxides by Worrell and Henshal (1978) and Zahra et al (1993), the 141 cm -1 peak has been attributed to a covalent Pb-O-Pb bond in an interconnected tetragonal pyramid PbO 4 . Also, this peak at 141 cm -1 can be correlated to the NMR results of Lee and Kim (2015) who observed that the proportion of Pb-O-Pb increases with the PbO content. The charge balancing in the PbO 4 pyramids was discussed in several X-Ray diffraction analysis (Morikawa et al, 1982, Imaoka et al, 1986.…”
Section: Very Low Frequency Observations and Assumptions About The Rsupporting
confidence: 76%
See 2 more Smart Citations
“…Through the comparison undertaken on lead silicates glasses and lead silicates crystals by Furkawa et al (1978) and on lead oxides by Worrell and Henshal (1978) and Zahra et al (1993), the 141 cm -1 peak has been attributed to a covalent Pb-O-Pb bond in an interconnected tetragonal pyramid PbO 4 . Also, this peak at 141 cm -1 can be correlated to the NMR results of Lee and Kim (2015) who observed that the proportion of Pb-O-Pb increases with the PbO content. The charge balancing in the PbO 4 pyramids was discussed in several X-Ray diffraction analysis (Morikawa et al, 1982, Imaoka et al, 1986.…”
Section: Very Low Frequency Observations and Assumptions About The Rsupporting
confidence: 76%
“…The similarity between the glass and the mineral leads us to think that in our glasses, Pb is a divalent cation in four fold coordination according to the crystalline reference and previous work (Fayon et al, 1999). Secondly, the XANES spectra are not really affected by the increase of PbO content in silicate, excepted for the first EXAFS oscillation which shows a slight increase in energy with increasing PbO content: that feature reflects that the medium-range organization around Pb is changing a little with increasing PbO content, and probably the Pb-O-Pb fraction could be increasing with the PbO content according to Lee and Kim (2015).…”
Section: Xanes Spectra At the Pb L 3 -Edgementioning
confidence: 68%
See 1 more Smart Citation
“…5 studies have directly detected FO species both in very low silica glass compositions where stoichiometry demands its presence and in systems with somewhat higher silica contents and cations with very high field strengths or lone pair electron structures (Hung et al, 2016;Kim et al, 2015;Lee and Kim, 2014); some 29 Si NMR and Raman spectroscopic studies of very low silica glasses have also strongly suggested that FO must be present to account for observed silicate species (Fayon et al, 1999;Fayon et al, 1998;Nasikas et al, 2012;Sen et al, 2009;Sen and Tangeman, 2008). There has been significant controversy over the XPS findings and accompanying re-analyses of previously published NMR spectra (Malfait, 2015;Nesbitt et al, 2015a;Nesbitt et al, 2015b), including concerns about accuracy of alkali silicate glass compositions and the vagaries of fitting of highly overlapped Gaussian components of both XPS and NMR spectra.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…silicates (Lee and Kim, 2014); estimates of about 60 to 1000 have been made from less direct spectroscopic data on a number of Mg and Ca silicates (Davis et al, 2011;Nesbitt et al, 2015a).…”
Section: Accepted Manuscriptmentioning
confidence: 99%